A STUDY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMAN 2 RUMBIO JAYA IN RETELLING FAIRY TALES - Angraini, Yesi; Ras, Fakhri; K, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This descriptive research was aimed to find out the ability of the first year students of SMA Negeri 2 Rumbio Jaya in retelling fairy tales. The research data were collected on July 2016. The subject of this research was class X1 consisted of 25 students. The data were collected by giving text to the students in term of fairy tales namely Putri Pandan Berduri, Keong Mas (The Golden Snail), Lutung Kasarung, Bunga Batu (The Stone Flower), and Bawang Merah dan Bawang Putih (Onion and Garlic). The students were asked to retell fairy tales in front of the class. During the students retelling the story, three raters were listening and checking the students’ performance. The students were given scores by three raters based on the five components of speaking namely pronunciation, grammar, vocabulary, fluency and comprehension. Based on the research findings, it was found out thatthe ability of the first year students in retelling fairy tales is in mediocre level with the mean score 45.92. Then, the result showed that no student was in excellent level and 3 students (12%) reached good level. Furthermore, 15 students (60 %) were in mediocre level. Moreover, 7 students (28%) were in poor level and no student got the score in very poor level.Key Words: Students’ Ability, Retelling, Fairy Tales